نموذج فاما وفرينش لاختبار العوامل الثلاث لأداء المحافظ التقليدية في بورصة ماليزيا. - ارحومة د. هاني نوري (Dirasat in Economics and Business, 2021)
The main objective of this research is to test whether the style factors employed by the Fama and French (1993) three-factor model adequately explain the performance of the conventional sub-portfolios sorted by market values and their Shariah-compliant counterparts in Bursa Malaysia over the examination period from 1 December 2005 to 30 November 2017. The test was conducted by regressing the monthly excess returns of the conventional and Shariah sub-portfolios on the monthly returns of the Fama and French (1993) factors, which are the market risk premium, the small-cap risk premium, and the value risk premium. The results revealed that the Fama and French (1993) three-factor model can significantly explain the performance of the four conventional sub-portfolios sorted by market value and their Shariah-compliant counterparts.